Avaliação da expansão de células estromais mesenquimais em biorreator de escoamento em Vórtices de Taylor (BEVT) - González Gil, Liseth Viviana (2015)
The mesenchymal stromal cells (CEMs), considered a promising alternative due to the characteristics of self-regeneration and differentiation potential, occur in small amounts in different tissues of an adult individual. Because of this and the need to obtain them in large quantities for use in clinical treatments, there has been a strong demand for new types of bioreactors for its large-scale cultivation. Thus, a suitable characterization of mass transfer and shear forces are necessary for the improvement of these bioreactors. In this scenario, the present study finality was to evaluate the hydrodynamic characteristics and oxygen transfer to the CEMs cultivation in a Taylor vortex flow bioreactor prototype (BEVT), designed for oxygenation through a silicone membrane. To evaluate the oxygen transfer characteristics measurements were performed by the dynamic method for obtaining the volumetric coefficient of global mass transfer (KTLA). The shear stress, generated at different rotation speed conditions, was estimated from literature correlations for Taylor flow. The results obtained with the use of KTLA membrane were relatively high with values between 4.80 and 11.53 h-1 in the rotation speed of the internal cylinder between 60 and 120 rpm. The shear stress showed low values in relation to other types of bioreactors, with lower values 1N / m2 for speeds between 60 and 90 rpm. BEVT Benefits were also observed considering the hydrodynamics presented in the vortex with the whirls size calculated by the Kolmogorov scale. The results of cultures of hMSC-TERT lineage adhered to the microcarrier Cultispher® S in alpha-MEM medium culture with 15% v/v fetal bovine serum were satisfactory, showing a suitable adaptation of the cells to the BEVT oxygenated and hydrodynamic environment. Was obtained a considered high specific growth rate (0,032 h-1) and a maximum expansion factor of 9 with the addition of microcarriers after 120 h of culture. Altogether, the results show that the BEVT fulfills the cultivation technology requirements required by the CEMs and becomes a convenient alternative to culture other adherent, susceptible to caking and hydrodynamic forces sensitive animal cells.